Key drivers controlling stable isotope variations in daily precipitation of Costa Rica: Caribbean Sea versus Eastern Pacific Ocean moisture sources - Sanchez-Murillo, Ricardo (2016)
2013-2017: International Atomic Energy Agency, Vienna, Austria, Project CRP 17947: Stable isotopes in precipitation and paleoclimatic archives in tropical areas to improve regional hydrological and climatic impact models